Inclusive pedagogy for English language learners: A handbook of research-informed practices - Verplaetse, Lorrie Stoops; Migliacci, Naomi (Routledge, 2017)
In this Handbook leading researchers, teacher educators, and expert practitioners speak to current and future educators and educational leaders in understandable language about the research that informs best practices for English language learners integrated into the K-12 public school system. Responding to current state and federal mandates that require educators to link their practices to sound research results, it is designed to help educators to define, select, and defend realistic educational practices that include and serve well their English language learning student populations. A critical and distinctive feature of this volume is its non-technical language that is accessible to general educators who have not been trained in the fields of second-language development and applied linguistics. Each chapter begins with a thorough discussion of the recommended practices, followed by a description of the research that supports these practices. The rigor of reported research is contained, but this research is written in a lay person’s terminology, accompanied by bibliographies for readers who wish to read about the research in technical detail. The volume is structured around four themes:• In the Elementary Classroom• In the Middle and Secondary Classroom• School and Community Collaboration• School and District Reform. Inclusive Pedagogy for English Language Learners is intended for current and future educational administrators, all educators who have a keen interest in school reform at the classroom, school, or district level, and staff developers, policy makers, parents and community groups, and anyone interested in the successful education of linguistically and culturally diverse students.
Keywords: dept.wll